PENTINGNYA PENDIDIKAN KARAKTER PADA SISWA SEKOLAH DASAR DI ERA 4.0 - sucia ningsih sucii (PRODI PGSD UNIVERSITAS PGRI DELTA, 2022)
The development of the world has entered the era of the industrial revolution 4.0. The industrial revolution 4.0 is marked by the ease of use of information, and therefore affects the behavior of students who are involved in imitating bad actions. Therefore, education in elementary schools at the age of 4.0 must be aligned with character building. Character education is the process of instilling morals and religion in students from an early age through habituation that strengthens and develops behavior. The purpose of this article is to describe education in the revolutionary era 4.0, to describe the importance of character education for elementary school students in the 4.0 era, and to describe how character education for elementary school students can be implemented to deal with moral, moral and ethical degradation in the 4.0 era. Character must be instilled from an early age.